2016
DOI: 10.1051/ijmqe/2016013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the GUM and Monte Carlo methods on the flatness uncertainty estimation in coordinate measuring machine

Abstract: Abstract. In engineering industry, control of manufactured parts is usually done on a coordinate measuring machine (CMM), a sensor mounted at the end of the machine probes a set of points on the surface to be inspected. Data processing is performed subsequently using software, and the result of this measurement process either validates or not the conformity of the part. Measurement uncertainty is a crucial parameter for making the right decisions, and not taking into account this parameter can, therefore, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Simulations were programmed using the Monte Carlo method [ 24 , 25 ] to determine the contribution of each parameter to the final uncertainty. The probability density distributions (PDD) of each factor were defined based on its calibration data or the characteristics of the process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations were programmed using the Monte Carlo method [ 24 , 25 ] to determine the contribution of each parameter to the final uncertainty. The probability density distributions (PDD) of each factor were defined based on its calibration data or the characteristics of the process.…”
Section: Resultsmentioning
confidence: 99%
“…The authors describe the model and analysis of a measurement system and the effects of its main error sources, namely the temperature and the misalignment of the devices or of the work piece and the master piece. The influence of the error sources was studied and an estimation of the uncertainty of the system was provided using simulations programmed using the Monte Carlo method [ 24 , 25 ], and finally the process improvement achieved when the measurement results were fed back into the manufacturing process is shown. A general approach for modelling the uncertainty associated with coordinate measuring systems (CMSs) is given in [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Meanwhile, the rise in complex part designs and the growing demands of tighter tolerances have led to the requirements of an established and an effective plan for inspection process on CMMs. According to previous studies, 68 there can be many factors as shown in Figure 1, which contribute to the measurement uncertainty of CMM results. These factors include sampling strategy, workpiece position and orientation, surface conditions, sensor type and configuration, and environment conditions.…”
Section: Sampling Strategy and Its Purposementioning
confidence: 97%
“…Balasubramanian et al [7] estimated uncertainty in angle measurement using the GUM method taking into consideration the geometrical errors, temperature, vibrations, and probing strategy. Using a comparison between these two methods (GUM and the MCM) to validate an uncertainty measurement model, has been proven to give consistent results, it's within this framework that Jalid proposed a comparison of these two methods on the estimation of flatness uncertainty [8] based on the orthogonal distance regression (ODR) that provided the parameters of the substitute plane and their uncertainties, then studied the influence of sample size on the flatness estimation and uncertainty [9].…”
Section: Introductionmentioning
confidence: 99%